2019
DOI: 10.1007/s10460-019-09932-3
|View full text |Cite
|
Sign up to set email alerts
|

The abandonment of maize landraces over the last 50 years in Morelos, Mexico: a tracing study using a multi-level perspective

Abstract: Understanding the causes of maize landrace loss in farmers' field is essential to design effective conservation strategies. These strategies are necessary to ensure that genetic resources are available in the future. Previous studies have shown that this loss is caused by multiple factors. In this longitudinal study, we used a collection of 93 maize landrace accessions from Morelos, Mexico, and stored at the International Maize and Wheat Improvement Center (CIMMYT) Maize Germplasm Bank, to trace back to the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
(43 reference statements)
1
35
0
1
Order By: Relevance
“…Dyer et al [13] estimated that the average number of maize varieties cultivated per farm in Mexico dropped from 1.43 to 1.22 in the recent 15 years. Consistently, a field survey in the Mexican state of Morelos, comparing seed collections made in 1967 and 2017 in the same study area, found that of the 66 farmer families originally cultivating 93 maize landraces, only 13 families still conserved a total of 14 landraces directly descended from the 1967 collection [60]. Likewise, while the maize race 'Jala' was historically the dominant maize grown in the valley of Jala in the state of Nayarit, Mexico, today it is grown by fewer than 20% of farmers and on only 5% of the maize cultivation area [61].…”
Section: Genetic Erosionsupporting
confidence: 52%
See 2 more Smart Citations
“…Dyer et al [13] estimated that the average number of maize varieties cultivated per farm in Mexico dropped from 1.43 to 1.22 in the recent 15 years. Consistently, a field survey in the Mexican state of Morelos, comparing seed collections made in 1967 and 2017 in the same study area, found that of the 66 farmer families originally cultivating 93 maize landraces, only 13 families still conserved a total of 14 landraces directly descended from the 1967 collection [60]. Likewise, while the maize race 'Jala' was historically the dominant maize grown in the valley of Jala in the state of Nayarit, Mexico, today it is grown by fewer than 20% of farmers and on only 5% of the maize cultivation area [61].…”
Section: Genetic Erosionsupporting
confidence: 52%
“…The reasons leading to maize landrace abandonment are often complex and include agronomical, ecological, economic and social factors. One of the major reasons for landrace abandonment is their substitution with modern cultivars, including improved OPVs and hybrids, introduced since the 1950s [60]. Farmers' preference for hybrids over landraces is mainly due to: (1) agronomy, e.g., higher yields or disease resistance; (2) market factors, e.g., uniformity of quality or processing properties; (3) policy, e.g., subsidies for hybrids coupled with agricultural extension; or (4) commercial seed systems that favor the provision of few improved varieties in large quantities, while landraces' seed exchange is based on relations among farmers, friends, families, communities, and markets [60,65,66].…”
Section: Genetic Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse culinary and cultural uses have been developed with this diversity (Fernández-Suárez et al 2013 ), and farmers can rely on it, especially in traditional settings, to retain their autonomy for seed production (Hoogendoorn et al 2018 ). However, the conservation of agrobiodiversity in the agricultural landscape is threatened by the expansion of modern agricultural production systems (including improved varieties), urbanization, climate change, environmental degradation, changes in consumers’ preferences, natural disasters and social conflicts (van de Wouw et al 2009 ; McLean-Rodríguez et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the circular model is a dynamic strategy that ensures maintenance of genetic integrity. This model has been interpreted and followed by other researchers (Piergiovanni and Laghetti, 1999;Hawkes et al, 2000;Tin et al, 2001;Enjalbert et al, 2011;CIP, 2015;McLean-Rodríguez et al, 2019); we are incorporating the concept of rematriation in this model.…”
Section: Methodsmentioning
confidence: 94%